Management of horn gore injury and urticaria in a dairy cow: A case report - Tijjani, Abdul Nasir; Muhammad, Abubakar Sadiq; Mohammed, Konto; Abba, Yusuf; Chung, Eric Lim Teik Chung Lim Teik; Adamu, Lawan; Osman, Abdinasir Yusuf; Saharee, Abdul Aziz; Lila, Mohammed Azmi Mohammed; Haron, Abdul Wahid; Abdullah, Faez Firdaus Jesse (Journal of Advanced Veterinary and Animal Research, 2015)
This paper reports how a 4-year old Friesien-Sahiwal cross cow weighing 380 kg with horn gore injury on the left labia of the vulva was managed at the Large Animal Clinic, University Putra Malaysia. The lacerated wound measuring about 4-cm long was originated as a result of horn goring from another cow two weeks prior presentation of the cow to the clinic. Physical examination of the cow incidentally revealed urticaria on the left ventro-lateral aspect of the neck suspected to be sequel of hypersensitivity. The wound was treated by topical application of a mixture of Iodine, Benacillin LA, Biomectin 1% and Ilium Dermapred made into cream. While the uticaria was treated by intramuscular injection of Chlorpheniramine maleate at 0.5 mg/kg bwt. Animal management, housing design and presence of sharp horns are some of the factors that can lead to physical traumatic injuries in dairy cows. http://dx.doi.org/10.5455/javar.2015.b93